Metabolic and performance responses of male runners wearing 3 types of footwear: Nike Vaporfly 4%, Saucony Endorphin racing flats, and their own shoes - Kim Hébert-Losier; Steven J. Finlayson; Matthew W. Driller; Blaise Dubois; Jean-François Esculier; Christopher Martyn Beaven (Elsevier, 2022)
Purpose: We compared running economy (RE) and 3-km time-trial (TT) variables of runners wearing Nike Vaporfly 4% (VP4), Saucony Endorphin lightweight racing flats (FLAT), and their habitual running (OWN) footwear. Methods: Eighteen male recreational runners (age = 33.5 ± 11.9 year (mean ± SD), peak oxygen uptake (VO2peak) = 55.8 ± 4.4 mL/kg·min) attended 4 sessions approximately 7 days apart. The first session consisted of a VO2peak test to inform subsequent RE speeds set at 60%, 70%, and 80% of the speed eliciting VO2peak. In subsequent sessions, treadmill RE and 3-km TTs were assessed in the 3 footwear conditions in a randomized, counterbalanced crossover design. Results: Oxygen consumption (mL/kg·min) was less in VP4 (from 4.3% to 4.4%, p ≤ 0.002) and FLAT (from 2.7% to 3.4%, p ≤ 0.092) vs. OWN across intensities, with a non-significant difference between VP4 and FLAT (1.0%-1.7%, p ≥ 0.292). Findings related to energy cost (W/kg) and energetics cost of transport (J/kg·m) were comparable. VP4 3-km TT performance (11:07.6 ± 0:56.6 mm:ss) was enhanced vs. OWN by 16.6 s (2.4%, p = 0.005) and vs. FLAT by 13.0 s (1.8%, p = 0.032). The 3-km times between OWN and FLAT (0.5%, p = 0.747) were similar. Most runners (n = 11, 61%) ran their fastest TT in VP4. Conclusion: Overall, VP4 improved laboratory-based RE measures in male recreational runners at relative speeds compared to OWN, but the RE improvements in VP4 were not significant vs. FLAT. More runners exhibited better treadmill TT performances in VP4 (61%) vs. FLAT (22%) and OWN (17%). The variability in RE (-10.3% to 13.3%) and TT (-4.7% to 9.3%) improvements suggests that responses to different types of shoes are individualized and warrant further investigation.